Genome Editing in iPSC-Based Neural Systems: From Disease Models to Future Therapeutic Strategies - McTague, Amy; Rossignoli, Giada; Ferrini, Arianna; Barral, Serena; Kurian, Manju A. (Frontiers in Genome Editing, 2021)
Therapeutic advances for neurological disorders are challenging due to limited accessibility of the human central nervous system and understanding of disease mechanisms. Many neurological diseases lack precision treatments, leading to significant disease burden and poor outcome for affected patients. Induced pluripotent stem cell (iPSC) technology provides human neuronal cells that facilitate disease modeling and development of therapies. The use of genome editing, in particular CRISPR-Cas9 technology, has extended the potential of iPSCs, generating new models for a number of disorders, including Alzheimer and Parkinson Disease. Editing of iPSCs, in particular with CRISPR-Cas9, allows generation of isogenic pairs, which differ only in the disease-causing mutation and share the same genetic background, for assessment of phenotypic differences and downstream effects. Moreover, genome-wide CRISPR screens allow high-throughput interrogation for genetic modifiers in neuronal phenotypes, leading to discovery of novel pathways, and identification of new therapeutic targets. CRISPR-Cas9 has now evolved beyond altering gene expression. Indeed, fusion of a defective Cas9 (dCas9) nuclease with transcriptional repressors or activation domains allows down-regulation or activation of gene expression (CRISPR interference, CRISPRi; CRISPR activation, CRISPRa). These new tools will improve disease modelling and facilitate CRISPR and cell-based therapies, as seen for epilepsy and Duchenne muscular dystrophy. Genome engineering holds huge promise for the future understanding and treatment of neurological disorders, but there are numerous barriers to overcome. The synergy of iPSC-based model systems and gene editing will play a vital role in the route to precision medicine and the clinical translation of genome editing-based therapies.